Inequalities in utilization of maternal health services in Ethiopia: evidence from the PMA Ethiopia longitudinal survey - Asebe Hagos; Misganaw Guadie Tiruneh; Melak Jejaw; Kaleb Assegid Demissie; Lemlem Daniel Baffa; Demiss Mulatu Geberu; Getachew Teshale; Tesfahun Zemene Tafere (Frontiers in Public Health)
BackgroundPrevious studies documented the existence of substantial inequalities in the utilization of maternal health services across different population subgroups in Ethiopia. Regularly monitoring the state of inequality could enhance efforts to address health inequality in the utilization of maternal health services. Therefore, this study aimed to measure the level of inequalities in the utilization of maternal health services in Ethiopia.MethodThe study used data from the Performance Monitoring for Action Ethiopia (PMA Ethiopia) dataset. Longitudinal data was collected from a weighted sample of 1966 postpartum women using multistage stratified cluster sampling techniques between November 2021 to October 2022. We assessed inequality in maternal health services using three indicators: antenatal care four (ANC), skilled birth attendants (SBA), and postnatal care (PNC). Age, economic status, education level, place of residence, and subnational regions were used as dimensions for measuring inequality. The analysis was conducted using Health Equity Assessment Toolkit Plus (HEAT Plus) software. We computed the summary measure of health inequality: Difference (D), Ratio (R), Population Attributable Risk (PAR), and Population Attributable Fraction (PAF).ResultThe simple summary measures of inequality difference (D) reported a high level of inequality in the utilization of maternal health services in ANC four, SBA, and PNC across economic, education, residence, and subnational regions. The difference (D) in maternal health service utilization between advantaged and disadvantaged population groups exceeded 20 percentage points in all four dimensions of inequality for the three maternal health indicators. Similarly, the complex summary measures of inequality (PAR and PAF) also showed high levels of inequality in the utilization of ANC four, SBA, and PNC across all four dimensions of inequality. However, there was no age-related inequality in the use of maternal health services.ConclusionA high level of socioeconomic and geographic area related inequality was observed in the utilization of ANC four, SBA, and PNC services in Ethiopia. Women from socioeconomically disadvantaged subgroups and women from disadvantaged geographic areas significantly lagged behind in the utilization of maternal health services. Therefore, implementing targeted interventions for the most disadvantaged groups can help to reduce inequality in accessing maternal health services.